Ali Nusrettin’in Dil, Tarih ve Eğitimle ilgili görüşleri-eserleri (Metin) - Top, Bekir (My University, 2010)
Ali Nusret, “Şahab” adlı şiir kitabıyla Tanzimat’la Servet-i Fünun arasında bir geçiş noktasıdır. İlk kaleme aldığı şiirlerinde Muallim Naci’nin etkisi gözlenir. Ağabeyi Cenab Şahabettin’in tesiriyle de Recaizade Mahmut Ekrem, Abdülhak Hamit Tarhan’ın etkisi şiirlerinde kendini hissettirir. Şiirleri Divan Edebiyatı geleneğinden beslenmekle birlikte Batı tesirinde gelişen yeni edebiyatın da izlerini taşımaktadır. Ali Nusret şairliği dışında çeşitli dergilerde yazdığı dil, edebiyat, sanat, tarih, bilim ve eğitimle ilgili makaleleriyle tanınmıştır. Bilimsel makalelerinde Avrupa’daki teknik gelişmelerden haber vermiş, yabancı dergilerden yaptığı çevirilerle dönemin ilmi ve teknolojik gelişmelerini ve yeni keşifleri millete tanıtmıştır. Dile, edebiyata, tarihe, sanata, estetiğe dair süslü bir dille yazdığı makaleleri vardır. Dilin sadeleştirilmesine karşı çıkmış, dil hatalarını affetmeyen bir dil üstadıdır. Eğitim sistemindeki aksaklıklara çözüm önerileri getirmiş, yenilikçi fikirleriyle dikkat çeken bir dilci ve eğitimci olmuştur. Özetle Ali Nusret Tanzimat, Servet-i Fünun ve Milli Edebiyat dönemlerini idrak etmiş, bu üç dönemin izlerini eserlerinde hissettirmiş bir şair ve edibimiz olması yönüyle önemli bir şahsiyettir. Eserleri, yaşadığı asra ışık tutacak ve döneminin dil,tarih, eğitim anlayışının idrak edilmesinde gelecek nesillere kaynaklık edecektir.

Ali Nusret, had been a transition point between Tanzimat and Servet-i Fünun with his book titled Şahab. In his first poems, one can observe the induction from Muallim Naci. With the effect of his elder brother, Cenab Şehabettin, Recaizade Mahmut Ekrem's and Abdülhak Hamit Tarhan's feel can be sensed in his works. In addition to that his poetry feeds from Divan Literature., he has the traces of new generation literature grown up in the Western induction. Ali Nusret, in exception to his poet identity has been renowned by his various publications in magazines in the format of language, literature, arts, history, science and education. He had informed his readers in his scientific papers of technical developments in Europe. With his translations from foreign magazines, he had introduced to the public, the epoch's scientific and technological advancements and most recent discoveries. He had publications on language, literature, history, arts and aesthetics written in an embellished manner. He had stood tall against simplifications in the formal language, and had been a linguistic expert who had no tolerance for linguistic errors. He had brought offers of resolutions to the lame points in the educatory system, and he had been an aspiring linguist and a tutor with his splendid innovative ideas. In summary, Ali Nusret had comprehended Tanzimat, Servet-i Fünun and National Literature eras. He had the readers feel the traces of this trio and had been a non-trivial personality as a poet and literary expert. His works shall illuminate the century he lived in, and will play the role of an important source to make comprehend the era's language, history and educatory concept.
Keywords: Türk Dili